Efektivitas Sistem Layanan Rujukan Terpadu (SLRT) di Dinas Sosial Kota Banjarbaru: Penelitian - Lydia Putri; Junaidy; Devia Hetty Hernany (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the effectiveness of SLRT at the Banjarbaru City Social Service and identify supporting and inhibiting factors. Using a descriptive qualitative approach, data were collected from five informants through observation, interviews, and documentation. Analysis was conducted through reduction, presentation, and drawing conclusions. The results indicate that SLRT is quite effective, with community participation reaching 80%, reflecting the program's success in reaching its targets and providing easy, fast, and reliable services. This success is also supported by effective inter-agency coordination. Supporting factors include a strong legal basis, officer response, and local government support. While obstacles include a lack of information, geographical constraints, and suboptimal inter-agency coordination.